Review of Musharakah Islamic Finance Articles in Indonesia-Malaysia Database and Scopus Bibliometrics - Mohamad Torik Langlang Buana; Nuradli Ridzwan Shah Mohd Dali; Abu Hassan Makmun; ‎ Firmansyah; Taufik Akbar (KnE Social Sciences, 2024)
Non-Indexed Publication